Change of phytomass of accumulation ecosystems of Priazov’ya spits influenced and uninfluenced by ungulates (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
The article presents data on the current stock of phytomass of peninsular accumulative system «Biryuchiy Island Spit – Fedotovа Spit» in the North Pryazov’ya. The impact of naturalized ungulates on meadow and psammophytic and steppe communities of Biryuchiy Island Spit is analyzed. The composition and aboveground phytomass of grazed plants (Biryuchiy Island Spit) and non-grazed plants (Fedotova Spit) phytocenoses are characterized. The dependence between site climate, ungulate density and total stocks of herbaceous feed is determined. Directions of vegetation adaptation to overgrazing on the area under study are specified. Seasonal changes in feed stocks and chemical composition of 10 background plants of the area, found in animals’ stomachs are analyzed.
Keywords: Biryuchiy Island Spit, Azov-Syvash National Nature Park, nature reserve «Fedotova Spit», Priazovsky National Nature Park.